Comparative Study of Cardiac Radiation Dose With Different Types of Surgery in Breast Cancer Patients - Sajjad Abbas Khairullah Al-Maliki; Alaa Hasan Mussttaf; Yahya Ali Desher Al-Haidary (Diyala Journal of Medicine, 2024)
Background: It has been demonstrated that radiation therapy lowers both the death rate from breast cancer and its recurrence. Precise calculation of the radiation dose is crucial for treating the target site as well as protecting vital organs like the heart since large doses of radiation therapy significantly increase patient morbidity and death. Objective: To compare the mean heart dose of radiation in breast cancer patients between breast-conserving surgery versus mastectomy, between different radiotherapy doses and fractionation schedules, and between right and left breast cancer irradiation. Patients and Methods: This is a cross-sectional descriptive retrospective comparative study that was conducted in Baghdad Radiotherapy Center from January 2018 to June 2018, carried on 174 breast cancer patients of different age groups selected randomly and their mean heart dose data collected from their files and database in Baghdad Radiotherapy Center. Results: The overall average of the mean dose was 372 cGy (range from 76.4 to 716.2). The greatest difference in the mean heart dose was between (BCS) patients who received 5000 cGy with regional nodal irradiation and (BCS) patients who received 4005 cGy also with regional nodal irradiation (difference in the mean is 639.8, the P – value <0.001). Regarding the side of breast cancer, the greatest difference in mean heart dose was seen between left and right breast cancer patients who did the same type of surgery (MRM) and received the same dose of radiotherapy (4256 cGy) (difference in the mean is 565cGy and the P – value <0.001). No statistically significant difference in the mean dose between breast-conserving surgery and mastectomy was recorded. Conclusion: The mean heart dose of radiotherapy is significantly increased in left-sided breast cancer irradiation as compared to the right side. A dose of 5000 cGy has the greatest effect on the dose received by the heart, especially in left breast cancer. The type of surgery whether breast-conserving surgery or mastectomy did not affect the mean dose received by the heart. Keywords: Breast cancer, cardiac radiation dose, breast cancer surgery, breast cancer treatment.